State corporations’ creation for more efficient management of public resources - S. A. Bannikov (Вестник университета)
In order to fulfill the tasks of sustainable state development, the creation of an innovative economy and the achievement of technological independence it is of particular importance to find ways to improve the efficiency of public resource management. Especially this concerns the development of measures to increase the impact of research and development, and the introduction of new technologies. As part of the implementation of this task, a statistical and economic analysis of the introduction effects of advanced production technologies at enterprises, including in the context of various forms of ownership has been carried out in the work. It is established that the best research results and development work are observed in companies with state participation, especially in state corporations. Thus, one of the most effective forms of innovation economy development in Russia is the further creation of state-owned companies in the most high-tech areas.